2017
DOI: 10.4195/nse2016.11.0032
|View full text |Cite
|
Sign up to set email alerts
|

Classroom versus Outdoor Biology Education Using a Woody Species Identification Digital Dichotomous Key

Abstract: The effectiveness of outdoor education in comparison to classroom (indoor) education and the acceptance of biology apps by students is still largely unknown. To bridge this gap, a quasi-experiment was performed with secondary school students within each of the schools. Students used a digital dichotomous key to identify woody species. One school performed outdoor identification and the other indoor identification. The students completed a pre-test and post-test on botanical knowledge, and they completed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Physical biology keys were also often provided to participants to help with identification (Unger et al, 2021). This is also important because the use of dichotomous digital biology keys has been shown to be successful in improving students' knowledge of species (Laganis et al, 2017;Torkar, 2021). The use of keys could therefore help students become familiar with an organism they are trying to identify (Jacquemart et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical biology keys were also often provided to participants to help with identification (Unger et al, 2021). This is also important because the use of dichotomous digital biology keys has been shown to be successful in improving students' knowledge of species (Laganis et al, 2017;Torkar, 2021). The use of keys could therefore help students become familiar with an organism they are trying to identify (Jacquemart et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One useful ICT for teaching biology is the digital biology key. Biology identification keys are very effective in improving students' knowledge of plant species names (Anđić et al, 2019;Laganis et al, 2017;Torkar, 2021). Thomas and Fellowes (2017) discovered that, even if there was no significant difference in obtaining species knowledge between using books and apps to identify species, mobile devices offered more opportunities for students to engage with the subject outside of the allocated teaching time due to their general portability and accessibility.…”
Section: Ict In Biology Educationmentioning
confidence: 99%
“…Alongside research on students at the university level of education and the contribution of the DIK to their knowledge or opinions, some researchers have conducted analogue studies with students in secondary and primary schools. Laganis et al (2017) explored the effectiveness of DIKs in outdoor and classroom plant identification by students in secondary schools. They concluded that the DIK provides to the students effective, interesting, experiential and convenient learning.…”
Section: The Dik As a Learning Toolmentioning
confidence: 99%
“…Priporočljivo je, da so študentje predhodno seznanjeni z učnimi gradivi, merilnimi napravami in s pripomočki za terensko delo. Vse uporabnejše postajajo uporabne različne brezplačne aplikacije za mobilno učenje (Anđić, Cvijetićanin, Maričić in Stešević, 2018;Anđić, Cvjetićanin, Lavicza, Maričić, Novović in Stešević, 2020;Ruchter, Klar in Geiger, 2010;Laganis, Prosen in Torkar, 2017;Thomas in Fellowes, 2017). Seznanjeni naj bodo tudi z ukrepi ob nesreči na terenu in osebnimi potrebščinami, kot so: oblačila, obutev, beležka, fotoaparat, prenočevanje, prehrana, denar itn.…”
Section: Priporočila Za Načrtovanje Izvedbo In Za Evalvacijo Terenskega Delaunclassified